Geographic Information System Design for Irrigation System Performance Index Main Network - Ernanda, Heru; Andriyani, Idah; Nadzirah, Rufiani; Indarto, Indarto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Irrigation plays an important factor in supporting agricultural land productivity to improve agricultural production. This is achieved by maintaining a sustainable irrigation system through an effective and efficient irrigation system. One method to asses is by using the Irrigation System Performance Index (IKSI). This study designs an information system for IKSI in the main network system. The assessment of IKSI follows PERMEN PU NO.32/2007, with parameters such as physical infrastructure assessment, crop productivity, supporting facilities, personnel organization, documentation, and P3A. The purpose of this system is to determine the operation and maintenance (O&M) strategies and non-physical management strategies. The Main Network SIG IKSI design includes functionalities such as (i) a data folder system, (ii) an imaging system, (iii) GIS, and (iv) an evaluator of physical and non physical irrigation systems. The results of the program in the Antirogo irrigation area show an IKSI the main network value for physical infrastructure of 85,0% and non physical strategies (crop productivity, supporting facilities, personnel organization, documentation, and P3A) of 70,0% until 80,0%. The results shows that the physical infrastructure needs to be carried out regularly and non-physical strategies need to be maintained and improved. Keywords: Association of Farmer Water Users, Geographic Information System, Irrigation System Performance Index, Irrigation, PAKSI.